A Multifaceted Evaluation of a COVID-19 Contact Tracing Program in King County, Washington. Issue 4 (July 2022) - Hood, Julia E.; Kubiak, Rachel W.; Avoundjian, Tigran; Kern, Eli; Fagalde, Meaghan; Collins, Hannah N.; Meacham, Elizabeth; Baldwin, Megan; Lechtenberg, Richard J.; Bennett, Amy; Thibault, Christina S.; Stewart, Sarah; et al.
Abstract : Context: Despite the massive scale of COVID-19 case investigation and contact tracing (CI/CT) programs operating worldwide, the evidence supporting the intervention's public health impact is limited. Objective: To evaluate the Public Health—Seattle & King County (PHSKC) CI/CT program, including its reach, timeliness, effect on isolation and quarantine (I&Q) adherence, and potential to mitigate pandemic-related hardships. Design: This program evaluation used descriptive statistics to analyze surveillance records, case and contact interviews, referral records, and survey data provided by a sample of cases who had recently ended isolation. Setting: The PHSKC is one of the largest governmental local health departments in the United States. It serves more than 2.2 million people who reside in Seattle and 38 other municipalities. Participants: King County residents who were diagnosed with COVID-19 between July 2020 and June 2021. Intervention: The PHSKC integrated COVID-19 CI/CT with prevention education and service provision. Results: The PHSKC CI/CT team interviewed 42 900 cases (82% of cases eligible for CI/CT), a mean of 6.1 days after symptom onset and 3.4 days after SARS-CoV-2 testing. Cases disclosed the names and addresses of 10 817 unique worksites (mean = 0.8/interview) and 11 432 other recently visited locations (mean = 0.5/interview) and provided contact information for 62 987 household members (mean = 2.7/interview) and 14 398 nonhousehold contacts (mean = 0.3/interview). The CI/CT team helped arrange COVID-19 testing for 5650 contacts, facilitated grocery delivery for 7253 households, and referred 9127 households for financial assistance. End of I&Q Survey participants (n = 304, 54% of sampled) reported self-notifying an average of 4 nonhousehold contacts and 69% agreed that the information and referrals provided by the CI/CT team helped them stay in isolation. Conclusions: In the 12-month evaluation period, CI/CT reached 42 611 households and identified thousands of exposure venues. The timing of CI/CT relative to infectiousness and difficulty eliciting nonhousehold contacts may have attenuated the intervention's effect. Through promotion of I&Q guidance and services, CI/CT can help mitigate pandemic-related hardships.